2004
DOI: 10.1007/s11894-004-0012-7
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune hepatitis in children

Abstract: Autoimmune hepatitis (AIH) remains an enigmatic condition that affects children of all ages. Although much knowledge has emerged over the past four decades regarding autoimmune diseases, the lack of a spontaneous animal model has hindered a more complete understanding of the pathophysiology of AIH. Serum autoimmune markers, combined with biochemical and histologic evidence of hepatocellular injury and absent other diagnostic considerations, are necessary to diagnose AIH. The clinical spectrum ranges from asymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
10
0
6

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 52 publications
8
10
0
6
Order By: Relevance
“…In the present study, biochemical liver tests (LFT) typically showed a "hepatitic" (with or without cholestatic) pattern of abnormalities, as serum aminotransferase activity and bilirubin concentrations varied widely from very mildly abnormal to more than 50 fold rise the upper normal limits in all patients with AILDs and cryptogenic chronic hepatitis, but the hyperbilirubinemia is notably cholestatic in all patients (100%) with overlap syndromes, as it was associated with alkaline phosphatase elevation more than 3 time the upper normal limit. This observation is in coincidence with many other studies [14,15,16], they classified overlap syndrome as an "intermediate level between cholestatic form of AIH or hepatic form of cholestatic syndromes". The hypergammaglobulinemia, which is the most reliable laboratory parameter in AILDs, was increased in this study in all patients with AILDs and much higher value were observed in type I AIH with average 2.5 g/dl, when compared to other types of AILDs, this observation also recorded by Porta and Squires [16,17].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In the present study, biochemical liver tests (LFT) typically showed a "hepatitic" (with or without cholestatic) pattern of abnormalities, as serum aminotransferase activity and bilirubin concentrations varied widely from very mildly abnormal to more than 50 fold rise the upper normal limits in all patients with AILDs and cryptogenic chronic hepatitis, but the hyperbilirubinemia is notably cholestatic in all patients (100%) with overlap syndromes, as it was associated with alkaline phosphatase elevation more than 3 time the upper normal limit. This observation is in coincidence with many other studies [14,15,16], they classified overlap syndrome as an "intermediate level between cholestatic form of AIH or hepatic form of cholestatic syndromes". The hypergammaglobulinemia, which is the most reliable laboratory parameter in AILDs, was increased in this study in all patients with AILDs and much higher value were observed in type I AIH with average 2.5 g/dl, when compared to other types of AILDs, this observation also recorded by Porta and Squires [16,17].…”
Section: Discussionsupporting
confidence: 86%
“…This observation is in coincidence with many other studies [14,15,16], they classified overlap syndrome as an "intermediate level between cholestatic form of AIH or hepatic form of cholestatic syndromes". The hypergammaglobulinemia, which is the most reliable laboratory parameter in AILDs, was increased in this study in all patients with AILDs and much higher value were observed in type I AIH with average 2.5 g/dl, when compared to other types of AILDs, this observation also recorded by Porta and Squires [16,17]. There was no statistically significant difference between the degree of liver function impairement and the presence of specific auto-antibody, indicating that these auto-antibodies should be used for diagnostic purpose only and they do not correlate with disease severity and activity and also similar to that as reported by Luxon [18].…”
Section: Discussionsupporting
confidence: 86%
“…Characteristic laboratory findings include the detection of antibodies against certain tissue antigens, elevated serum liver enzymes and gamma globulins [1,2]. Histological examination usually reveals mononuclear cell infiltration in the portal tracts with fibrosis and/or cirrhosis to a variable extent.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of these issues in most countries systematic epidemiological data are not available to date. Nevertheless, these informations are the basis for synchronization of treatment, determination of prognostic factors and improvement of longterm outcome [2,8].…”
Section: Introductionmentioning
confidence: 99%
“…AIH is diagnosed based on the presence of autoimmune serum markers, combined with biochemical and histologic evidence of hepatocellular injury and the absence of other diagnostic (2). Currently, AIH is thought to be the result of self-perpetuating autoimmune processes triggered by yet unknown factors (e.g., infections, chemicals, drugs) in a genetically susceptible host (3).…”
Section: Discussionmentioning
confidence: 99%